BEHIND THE SACRED TREE: LOCAL PEOPLE AND THEIR NATURAL RESOURCES SUSTAINABILITY - Royyani, Mohammad; Rahajoe, Joeni (REINWARDTIA, 2014)
Local communities have their own means of maintaining their traditional know-ledge and sustaining the production system of natural resources by designating the resources as sacred. Without the states influence, local people have their own strategies to conserve the environment and resources, in ways which are more effective than those enforced by the state. A study done through interview, participatory observation, and ethnographic methods revealed that local people recognized two models of natural resources conservation. The first model is the designation of forests as sacred site, aiming at maintaining the sustainability of ecosystem and the second model refers to adoption of species as a sacred entity to sustain production system. Dynamic processes are operating in the sacredness of both forest and species.